Trend Research Analysis of Economic Growth Theory for Developing an Islamic Perspective Theory - Siti Murtiyani; Nunung Nurlaela (Journal of Islamic Economic and Business Research, 2025)
The formulation of the theory of economic growth is still a serious debate and continues to develop towards its maturity. This study aims to map the evolution of economic growth theory and to reposition Islamic economic growth, particularly those related to nexus theory, wellbeing economy, and Beyond GDP frameworks. The study employs a bibliometric analysis of scholarly articles on economic growth theory published between 2000 and 2024, using Google Scholar as the primary database and VOSviewer for keyword co-occurrence and thematic clustering. The bibliometric findings are complemented by a conceptual analysis to develop an Islamic economic growth framework that engages with recent theoretical developments. The results reveal a significant shift in economic growth research from GDP-centered models toward nexus-based and post-GDP paradigms. The bibliometric analysis identifies key thematic clusters related to energy–growth nexus, inclusive growth, inequality, and wellbeing economy. Building on these trends, the study proposes an Islamic economic growth framework that functions as a corrective mechanism by integrating poverty and income inequality into growth assessment. This study contributes to the literature by reframing Islamic economic growth as a parsimonious corrective framework. By retaining GDP as a measure of productive capacity while correcting it through distributive indicators, the proposed approach bridges Islamic economic principles with contemporary growth debates and offers a conceptually grounded and policy-relevant contribution. This study is conceptual in nature and does not empirically test the proposed correction framework. Future research may empirically examine the applicability of the model across countries and refine the weighting of poverty and inequality indicators to enhance contextual relevance.